Compression Of Hyperspectral Images: A Comparative Study - Parlak, Cevahir; Bilgin, Gokhan (IEEE, 2014)
In this study, theoretical and practical aspects of hyperspectral image compression is handled and SPIRT, SPIHT 3D, STW, ASWDR, EZW, DCT, JPEG, MP3, M4A methods are presented comparatively. Results are provided for the entire cube instead of some certain part of the full cube, contrary to the most of the work in this field. For this purpose, entire hyperspectral cube which consists of 200 bands was divided into 50 parts, each of them containing 4 successive bands of the cube and coded as 24bit true color bitmap. For MP3 and M4A, the entire cube is transformed into a one dimensional Wave file. Results are presented as the average of the sum of PSNR, CR, MSE, BPP of these 50 bitmaps.
Keywords: Hyperspectral images; compression; AVIRIS; image cube; Engineering; Telecommunications